The Competency of Human Resources in Relation to Internal Control - Ela Siti Nurpajriah; Siti Kustinah (Portofolio: Jurnal Ekonomi, Bisnis, Manajemen, dan Akuntansi, 2021)
Abstract To create human beings into human capital in an organization requires intellectual capital, which consists of the abilities they have and the ability to use them at work. Intellectual capital, which is the value of human resources, plays an important role and requires transformation more than just carrying out administrative functions but includes overall strategy, administration and as a liaison with top management who are responsible for organizational performance. One of the criteria for achieving the best performance in a company is the achievement of goals. internal control. One of the achievements of internal control objectives is through the ability or competence of employees. Employee competencies that must be possessed by these employees are ability in the field of good planning, ability to give the best influence on others, ability to communicate well, ability to open social networks, ability to think logically and ability to organize or managerial skills. Abstrak Untuk menjadikan manusia menjadi modal manusia dalam suatu organisasi diperlukan modal intelektual, yang terdiri dari kemampuan yang mereka miliki dan kemampuan untuk menggunakannya dalam bekerja. Intellectual capital yang merupakan nilai sumber daya manusia, memegang peranan penting dan memerlukan transformasi lebih dari sekedar menjalankan fungsi administratif tetapi mencakup keseluruhan strategi, administrasi dan sebagai penghubung dengan manajemen puncak yang bertanggung jawab atas kinerja organisasi. Salah satu kriteria pencapaian kinerja terbaik dalam suatu perusahaan adalah tercapainya tujuan. pengendalian internal. Salah satu pencapaian tujuan pengendalian intern adalah melalui kemampuan atau kompetensi pegawai. Kompetensi pegawai yang harus dimiliki pegawai tersebut adalah kemampuan dalam bidang perencanaan yang baik, kemampuan memberikan pengaruh terbaik kepada orang lain, kemampuan berkomunikasi dengan baik, kemampuan membuka jejaring sosial, kemampuan berpikir logis dan kemampuan berorganisasi atau manajerial.